Formative assessment in Physical Education and its relation to the level of attention of primary school children - Carrillo-López, Pedro José; Maneiro-Dios, Rubén; Moral-García, José Enrique (Specijalna edukacija i rehabilitacija, 2022)
Introduction. The aim of this study was to analyse the relationship between primary school students’ perception of the Physical Education teacher’s formative assessment practices in terms of their level of attention. Methods. In this descriptive cross-sectional study that included 172 students, attention was assessed through the Perception of Similarities and Differences test and the teacher’s formative assessment practices through the teacher performance questionnaire associated with formative assessment practices whose scores were validated. Results. With regard to gender, Student’s t-test showed no significant differences except for the number of errors in favour of males (p < .05). In relation to the level of attention, we detected statistically significant differences in metacognitive (p < .05) and retrospective (p < .05) formative assessment in favour of those with a lower level of attention. However, the linear regression test showed a negative association between attention and metacognitive formative assessment (R2 = .28). Conclusion. It can be concluded that a lower level of attention seems to be associated with a higher perception of primary school students of metacognitive assessment practice associated with internal information processing and with retroactive assessment practice, which is related to the anticipation of learning difficulties. Being aware of the importance of formative assessment in the teaching-learning process, it would be advisable to involve the whole educational community in order to arouse interest among teachers, as it provides essential knowledge in their professional work, contributing to the improvement of academic development as well as to the comprehensive training of all schoolchildren.
Keywords: attention; formative assessment; schoolchildren; Physical Education; education